Thermoplastic elastomer composition, injection molded product and airbag storage cover

A thermoplastic elastomer composition with propylene block copolymer and ethylene α-olefin copolymer, optimized for low temperature impact resistance and reduced glossiness, addresses the limitations of existing materials by enhancing design and mechanical properties in airbag storage covers.

JP7622383B2Active Publication Date: 2025-01-28MITSUBISHI CHEM CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2020156439
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-09-17
Publication Date
2025-01-28
Estimated Expiration
2040-09-17

AI Technical Summary

Technical Problem

Existing thermoplastic elastomer compositions used in airbag storage covers are inadequate for maintaining low temperature impact resistance and design appearance, particularly in low temperature ranges, and the painting process can lead to issues like paint line expansion and high glossiness.

Method used

A thermoplastic elastomer composition containing propylene block copolymer and ethylene α-olefin copolymer, with specific properties such as a dice wel ratio of 1.10 or more, glossiness of 50% or less, and bending elasticity of 100-700 MPa, achieved through dynamic heat treatment with organic peroxide and bridging agents.

Benefits of technology

The composition enables the production of airbag storage covers with excellent design and low temperature impact resistance, reducing glossiness and improving flowmark properties while maintaining mechanical strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007622383000001
    Figure 0007622383000001
Patent Text Reader

Abstract

To provide a thermoplastic elastomer composition capable of forming a moded product having excellent designability while maintaining low temperature impact resistance.SOLUTION: There is provided a thermoplastic elastomer composition which comprises the following components (A) and (B), wherein the die swell ratio (at a test temperature of 210°C and a shear rate of 243 / s) in a capillary rheometer (JIS K7199) is 1.10 or more. The glossiness measured at an incident angle of 60° according to ISO 2810 for a specimen for gloss measurement composed of the thermoplastic elastomer composition is 50% or less and the flexural modulus measured according to ISO 178 (2010) for a specimen for flexural modulus measurement composed of the thermoplastic elastomer composition is 100 to 700 MPa. Component (A): a propylene-based block copolymer, Component (B): an ethylene-α-olefin copolymer.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermoplastic elastomer composition, and an injection-molded article and an airbag storage cover made of this thermoplastic elastomer composition. [Background technology]

[0002] Automotive airbag systems protect drivers and passengers in the event of a collision, and consist of a device that detects the impact of a collision and an airbag device. The airbag device is installed in the steering wheel, the instrument panel in front of the passenger seat, the driver's and passenger's seats, the front and side pillars, etc.

[0003] Various proposals have been made regarding the structure and material of an airbag storage cover in an airbag device so that the cover will tear as designed when the airbag inflates.

[0004] As an airbag storage cover made of an olefin-based thermoplastic elastomer, for example, Patent Document 1 proposes a thermoplastic elastomer composition obtained by dynamically heat-treating a composition containing a specific propylene-based polymer, a specific olefin-based block copolymer, and a specific amount of a styrene-conjugated diene block copolymer and / or a hydrogenated product thereof in the presence of an organic peroxide. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2016-186041 A Summary of the Invention [Problem to be solved by the invention]

[0006] In recent years, there is concern that airbag storage covers may break in low temperature ranges due to improved airbag deployment power, and therefore materials with excellent low-temperature impact resistance are desired from the viewpoints of improved safety, freedom of design, etc. In addition, airbag storage covers have traditionally been manufactured through a painting process, but there are problems with the cost of the painting process, such as the need to install additional painting lines, and in order to manufacture them more cheaply, materials that can be manufactured without painting have been desired in recent years. Furthermore, compared to unpainted airbag storage covers, molded products with low gloss and improved flow mark properties are desired from the viewpoint of design.

[0007] According to detailed studies by the present inventors, it has been found that the thermoplastic elastomer composition described in Patent Document 1 has problems such as poor flow mark resistance and insufficient appearance. The present invention has been made in consideration of the above problems of the conventional technology. That is, an object of the present invention is to provide a thermoplastic elastomer composition which enables the production of molded articles having excellent design while maintaining low-temperature impact resistance. [Means for solving the problem]

[0008] As a result of intensive investigations into the solution of the above-mentioned problems, the present inventors have found that the above-mentioned problems can be solved by a thermoplastic elastomer composition containing a propylene-based block copolymer and an ethylene / α-olefin copolymer, which has a die swell ratio (test temperature 210°C, shear rate 243 / s) of 1.10 or more as measured with a capillary rheometer (JIS K7199) (test temperature 210°C, shear rate 243 / s), a gloss of 50% or less measured at an incidence angle of 60°, and a flexural modulus of 100 to 700 MPa.

[0009] That is, the gist of the present invention resides in the following [1] to [7].

[0010] [1] A thermoplastic elastomer composition comprising the following components (A) and (B): A thermoplastic elastomer composition having a die swell ratio (test temperature 210°C, shear rate 243 / s) of 1.10 or more as measured using a capillary rheometer (JIS K7199), a gloss of 50% or less as measured at an incidence angle of 60° according to ISO 2813 using a test piece for gloss measurement made of the thermoplastic elastomer composition, and a flexural modulus of 100 to 700 MPa as measured in accordance with ISO 178 (2010) using a test piece for flexural modulus measurement made of the thermoplastic elastomer composition. Component (A): Propylene block copolymer Component (B): Ethylene-α-olefin copolymer

[0011] [2] The thermoplastic elastomer composition according to [1], wherein the α-olefin of component (B) has 4 to 8 carbon atoms.

[0012] [3] The thermoplastic elastomer composition according to [1] or [2], wherein the ethylene-α-olefin copolymer of component (B) is an ethylene-α-olefin block copolymer.

[0013] [4] The thermoplastic elastomer composition according to [3], wherein the ethylene-α-olefin block copolymer is an ethylene-α-olefin block copolymer comprising a polymer block composed of ethylene and an ethylene-α-olefin copolymer block.

[0014] [5] The thermoplastic elastomer composition according to [4], wherein the ethylene-α-olefin block copolymer has a crystalline melting peak at 110 to 125°C and a heat of crystalline melting of 20 to 60 J / g.

[0015] [6] An injection-molded article obtained by injection molding the thermoplastic elastomer composition according to any one of [1] to [5].

[0016] [7] An airbag storage cover using the thermoplastic elastomer composition according to any one of [1] to [5]. Effect of the Invention

[0017] According to the present invention, it is possible to provide a thermoplastic elastomer composition which enables the production of molded articles having excellent design while maintaining low-temperature impact resistance. The airbag storage cover made of the molded product of the present invention can be suitably used as any of a driver's seat airbag storage cover, a passenger seat airbag storage cover, a pedestrian airbag storage cover, a knee airbag storage cover, a side airbag storage cover, a curtain airbag storage cover, etc. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The present invention will be described in detail below, but the present invention is not limited to the following description, and can be modified as desired without departing from the gist of the present invention. In this specification, when a numerical value or physical property value is enclosed before and after "~", the value before and after the "~" is included.

[0019] In the present invention, the term "airbag storage cover" refers to the container that stores an airbag in general, and is, for example, the opening through which the airbag deploys in a container that stores an airbag, or the entire container that is integrated with this opening.

[0020] [Thermoplastic elastomer composition] The thermoplastic elastomer composition of the present invention is a thermoplastic elastomer composition containing the following components (A) and (B), which has a die swell ratio (test temperature: 210°C, shear rate: 243 / s) (hereinafter, sometimes simply referred to as "die swell ratio") of 1.10 or more in a capillary rheometer (JIS K7199), a gloss (hereinafter, sometimes simply referred to as "gloss") measured at an incident angle of 60° according to ISO 2810 on a test piece for gloss measurement made of the thermoplastic elastomer composition is 50% or less, and a flexural modulus (hereinafter, sometimes simply referred to as "flexural modulus") measured on a test piece for flexural modulus measurement made of the thermoplastic elastomer composition according to ISO 178 (2010) is 100 to 700 MPa. Component (A): Propylene block copolymer Component (B): Ethylene-α-olefin copolymer

[0021] In order to set the die swell ratio, gloss and flexural modulus within the above-specified ranges, the thermoplastic elastomer composition of the present invention is preferably produced by dynamically heat treating a composition containing the above-mentioned components (A) and (B) in the presence of the following components (C) and (D). Component (C): Organic peroxide Component (D): Crosslinking agent

[0022] <Die swell ratio> It has been found that the thermoplastic elastomer composition of the present invention tends to have good flow mark properties when the die swell ratio is 1.10 or more. It is believed that when the thermoplastic elastomer composition of the present invention has a die swell of 1.10 or more, the flow front in the mold during injection molding becomes stable, improving the flow mark properties. The die swell ratio of the thermoplastic elastomer composition of the present invention is preferably 1.13 or more, more preferably 1.15 or more. There is no upper limit to the die swell ratio of the thermoplastic elastomer composition, but it is usually 2.00 or less.

[0023] In the present invention, the die swell ratio in a capillary rheometer (JIS K7199) is a value measured during the extrusion process of a sample under the following conditions using a Capillograph 1D (JIS K7199) manufactured by Toyo Seiki Seisakusho Co., Ltd., and is calculated by the following calculation formula (I). Test temperature: 210℃ L / D: 10 (D=1mm) Shear rate: 243 / s St=Dm / Dt (I) St, Dm, and Dt indicate the following. St: Die swell ratio Dm: diameter of extrusion sample measured at test temperature, 10 mm below the die exit (mm) Dt: diameter of the capillary die measured at the test temperature (mm)

[0024] In order to make the die swell ratio of the thermoplastic elastomer composition containing the above-mentioned components (A) and (B) 1.10 or more, it is preferable to take the following measures, for example. From the viewpoint of the manufacturing method, it is preferable to dynamically heat-treat a mixture of a part of component (A), component (B), components (C) and (D) described below, and if necessary, components (E) and (F) described below to partially crosslink the mixture, and then add the remainder of component (A). In this way, the component (A) added later is less susceptible to molecular chain scission by radicals, the tensile strength of the composition can be maintained high, and the die swell ratio can be controlled to 1.10 or more. The part of component (A) and the remainder of component (A) may be one or more kinds as long as they correspond to the component (A) described below, and the part of component (A) and the remainder of component (A) may be the same or different. As components to be added after partial crosslinking by dynamic heat treatment, it is considered that the die swell ratio can be increased by component (B), component (E) and component (F) in addition to component (A). Therefore, with regard to component (B), component (E) and component (F), one or more of these may be partially added and mixed before partial crosslinking by dynamic heat treatment, and the remainder may be added after partial crosslinking by dynamic heat treatment.

[0025] <Glossiness> The gloss of the thermoplastic elastomer composition of the present invention measured at an incidence angle of 60° is 50% or less. If the gloss is equal to or less than the upper limit, the desired design can be obtained without painting. The upper limit of the gloss is preferably 40% or less, more preferably 35% or less.

[0026] The gloss level in the present invention is a value measured in accordance with ISO 2813 at an incidence angle of 60° by molding a test piece for gloss measurement (a sheet having a thickness of 2 mm, a width of 120 mm, and a length of 80 mm) from the thermoplastic elastomer composition using an in-line screw type injection molding machine at an injection speed of 30 mm / s, a cylinder temperature setting of 220°C, and a mold temperature of 40°C.

[0027] In the present invention, in order to adjust the gloss of the thermoplastic elastomer composition to the above upper limit or less, it is preferable to subject a composition containing components (A) and (B) to dynamic heat treatment in the presence of components (C) and (D) described below.

[0028] <Flexural modulus> The thermoplastic elastomer composition of the present invention has a flexural modulus of 100 to 700 MPa. In the present invention, the flexural modulus is correlated with low-temperature impact resistance, and by setting the flexural modulus within the above range, excellent low-temperature impact resistance can be achieved while maintaining the shape retention of the molded article. From the viewpoint of low-temperature impact resistance, the upper limit of the flexural modulus is preferably 600 MPa or less, more preferably 500 MPa or less. From the viewpoint of shape retention of the molded article, the lower limit of the flexural modulus is preferably 150 MPa or more, more preferably 200 MPa or more.

[0029] The flexural modulus in the present invention is a value measured at a speed of 2 mm / min in accordance with ISO 178 (2010) using a Pentograph B-2 manufactured by Toyo Seiki Co., Ltd., using a multipurpose evaluation test piece A (dumbbell having a length of 180 mm) conforming to ISO 3167 (2002) molded from the thermoplastic elastomer composition of the present invention using an in-line screw type injection molding machine at an injection speed of 30 mm / s, a cylinder set temperature of 220°C, and a mold temperature of 40°C, and then using a test piece for measuring the flexural modulus (thickness 4 mm × width 10 mm × length 80 mm) prepared by cutting off the ends of the dumbbell.

[0030] In the present invention, in order to set the flexural modulus of the thermoplastic elastomer composition in the above range, it is preferable to use components (A) and (B) as materials and mix them in the preferred ranges described below.

[0031] <Component (A)> The thermoplastic elastomer composition of the present invention contains a propylene-based block copolymer as component (A). The propylene unit content of the propylene-based block copolymer of component (A) is usually more than 50% by mass, preferably 70 to 99% by mass, based on the entire component (A). When the propylene unit content of component (A) is equal to or more than the above lower limit, the heat resistance and rigidity tend to be good. When the propylene unit content of component (A) is equal to or less than the above upper limit, the low-temperature impact resistance tends to be good. When component (A) is constituted by mixing two or more propylene-based polymers having different compositions, the propylene unit content of component (A) as a whole may be within the above numerical range.

[0032] The propylene unit content and the α-olefin unit content described below in component (A), and the ethylene unit content and the α-olefin unit content described below in component (B) can each be determined by infrared spectroscopy.

[0033] Component (A) contains propylene units in the above-mentioned preferred content relative to the entire component (A), and also contains ethylene units other than propylene units, α-olefin units other than propylene (hereinafter sometimes referred to as "other α-olefins") units, monomer units other than ethylene and α-olefins, etc. Examples of the propylene-based block copolymer of component (A) include propylene-ethylene block copolymers, propylene-other α-olefin block copolymers, propylene-ethylene-other α-olefin block copolymers, and other propylene-based block copolymers.

[0034] The total content of ethylene units other than propylene units, other α-olefin units and other monomer units in component (A) is preferably 1 to 30 mass %.

[0035] When component (A) is a propylene-other α-olefin block copolymer, the α-olefin units other than propylene can include α-olefin units having 4 to 20 carbon atoms. Examples of α-olefins having 4 to 20 carbon atoms include 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, 1-eicosene, 3-methyl-1-butene, 3-methyl-1-pentene, 4-methyl-1-pentene, 2-ethyl-1-hexene, and 2,2,4-trimethyl-1-pentene. The α-olefin other than propylene is preferably an α-olefin having 4 to 10 carbon atoms, more preferably 1-butene, 1-hexene, or 1-octene. These other α-olefin units may be contained in component (A) either alone or in combination of two or more kinds.

[0036] Examples of the propylene-based block copolymer of component (A) include a propylene-ethylene block copolymer, a propylene-1-butene block copolymer, a propylene-1-hexene block copolymer, a propylene-1-octene block copolymer, a propylene-ethylene-1-butene block copolymer, a propylene-ethylene-1-hexene block copolymer, a propylene-ethylene-1-octene block copolymer, and a propylene-based block copolymer obtained by polymerizing a propylene homopolymer in a first step and subsequently polymerizing a propylene-ethylene block copolymer in a second step.

[0037] Preferred are block copolymers of propylene and at least one monomer selected from ethylene and α-olefins having 4 to 10 carbon atoms, and propylene-based block copolymers obtained by polymerizing a propylene homopolymer in a first step and subsequently polymerizing a propylene-ethylene copolymer in a second step. Among these, in terms of low-temperature impact resistance and high-temperature strength, it is particularly preferred that component (A) is a propylene-based block copolymer obtained by polymerizing a propylene homopolymer in a first step and subsequently polymerizing a propylene-ethylene copolymer in a second step.

[0038] The melt flow rate (230°C, load 21.18N) of component (A) is not limited, but is usually 0.1g / 10min or more, and from the viewpoint of the appearance of the molded product, it is preferably 10g / 10min or more, more preferably 20g / 10min or more, and even more preferably 30g / 10min or more. The melt flow rate (230°C, load 21.18N) of component (A) is usually 200g / 10min or less, and from the viewpoint of tensile strength, it is preferably 150g / 10min or less, more preferably 100g / 10min or less. The melt flow rate (MFR) of component (A) is measured under the conditions of 230°C and load 21.18N according to ISO 1133 (2011). A plurality of components (A) having a melt flow rate (230° C., load 21.18 N) within the range of 0.1 to 200 g / 10 min may be used.

[0039] The propylene block copolymer of component (A) can be produced by a known polymerization method using a known olefin polymerization catalyst. For example, a polymerization method using a Ziegler-Natta catalyst can be used. The polymerization method can be a slurry polymerization method, a solution polymerization method, a bulk polymerization method, a gas phase polymerization method, or the like, or two or more of these methods can be combined.

[0040] In addition, a commercially available product may be used as component (A). Examples of commercially available products of component (A) include "PrimPolypro (registered trademark)" manufactured by Prime Polymer Co., Ltd., "Sumitomo Noblen (registered trademark)" manufactured by Sumitomo Chemical Co., Ltd., "Polypropylene block copolymer" manufactured by SunAllomer Co., Ltd., "Novatec (registered trademark) PP" manufactured by Japan Polypropylene Corporation, "Moplen (registered trademark)" manufactured by LyondellBasell Co., Ltd., "ADFLEX (registered trademark)" manufactured by LyondellBasell Co., Ltd., "Hifax (registered trademark)" manufactured by LyondellBasll Co., Ltd., "ExxonMobil PP" manufactured by ExxonMobil Co., Ltd., "Formolene (registered trademark)" manufactured by Formosa Plastics Co., Ltd., and "B Examples of such polypropylene include "Borealis PP" manufactured by Orealis, "SEETEC PP" manufactured by LG Chemical, "ASIPOLYPROPYLENE" manufactured by A. Schulman, "INEOS PP" manufactured by INEOS Olefins & Polymers, "Braskem PP" manufactured by Braskem, "Hanwha Total" manufactured by Hanwha TOTAL PETROCHEMICALS, "Sabic (registered trademark) PP" manufactured by Sabic, "TOTAL PETROCHEMICAL SPolypropylene" manufactured by TOTAL PETROCHEMICALS, and "YUPLENE (registered trademark)" manufactured by SK Corporation.

[0041] The propylene-based block copolymer of component (A) may be used alone or in combination of two or more types having different copolymer component compositions, physical properties, and the like.

[0042] <Ingredient (B)> The thermoplastic elastomer composition of the present invention contains an ethylene-α-olefin copolymer as component (B). When the sum of the ethylene unit content and the α-olefin unit content is taken as 100% by mass, the ethylene-α-olefin copolymer of component (B) preferably has an ethylene unit content of 50 to 80% by mass and an α-olefin unit content of 20 to 50% by mass. When the ethylene unit content is within the above range, the affinity with other components is good, and the fine dispersibility of the thermoplastic elastomer composition tends to be improved.

[0043] The α-olefin constituting the ethylene-α-olefin copolymer of component (B) is not limited, but specific examples include propylene, 1-butene, 3-methyl-1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-octene, and 1-decene. Component (B) may contain only one type of these α-olefin units, or may contain two or more types. Among these, α-olefins having 4 to 8 carbon atoms are preferred, and 1-octene is more preferred. The ethylene-α-olefin copolymer contains 1-octene units as α-olefin units, which improves the tensile strength.

[0044] Examples of the ethylene-α-olefin copolymer of component (B) include ethylene-α-olefin random copolymers and ethylene-α-olefin block copolymers. Among these, ethylene-α-olefin block copolymers, particularly ethylene-α-olefin block copolymers containing a polymer block composed of ethylene and an ethylene-α-olefin copolymer block, are preferred.

[0045] Ethylene-α-olefin block copolymers have polymer blocks made of crystalline ethylene, and also have amorphous properties due to blocks containing α-olefin. By having component (B) have such a structure, it becomes easier to impart the effects of high temperature strength and low temperature impact resistance to the obtained airbag storage cover. Furthermore, it is believed that the polymer block made of ethylene is dynamically heat-treated in the presence of an organic peroxide, component (C) described below, thereby lowering the gloss and improving the appearance.

[0046] The ethylene-α-olefin block copolymer of component (B) preferably has a crystalline melting peak at 110 to 125°C and a crystalline melting heat of 20 to 60 J / g. Here, component (B) having a crystalline melting peak at 110 to 125°C and a crystalline melting heat of 20 to 60 J / g calculated from the crystalline melting peak is an indicator that component (B) has a polymer block made of crystalline ethylene. From the viewpoint of high-temperature strength, the crystalline melting heat of component (B) is more preferably 30 J / g or more. Also, from the viewpoint of low-temperature impact resistance, the crystalline melting heat of component (B) is more preferably 50 J / g or less.

[0047] The amorphousness due to the α-olefin-containing blocks of the ethylene-α-olefin block copolymer of component (B) can be represented by the glass transition temperature. The glass transition temperature of component (B) measured by the DSC method is preferably −80° C. or higher, more preferably −75° C. or higher, and on the other hand, is preferably −50° C. or lower, more preferably −60° C. or lower.

[0048] The crystalline melting peak temperature, crystalline melting heat, and glass transition temperature of component (B) can be determined by differential scanning calorimetry (DSC). The crystalline melting peak temperature is the top temperature of the melting peak obtained by a differential scanning calorimeter (DSC), and the crystalline melting heat can be determined from the area of ​​the melting peak obtained by a differential scanning calorimeter. The glass transition temperature is the intersection point of the tangent at the inflection point and the baseline obtained by a differential scanning calorimeter. The specific measurement conditions for determining these values ​​are as follows: That is, a 10 mg sample is taken and melted using a DSC at a heating rate of 100°C / min from 25°C to 200°C, held at 200°C for 1 minute, crystallized at a heating rate of 10°C / min to -130°C, held at -130°C for 10 minutes, and then measured at a heating rate of 10°C / min up to 200°C.

[0049] The polymer block made of ethylene in the ethylene-α-olefin block copolymer of component (B) is mainly made of ethylene units, but may have other monomer units in addition to ethylene. Here, "mainly made of" means that it accounts for 50% by mass or more of the total, particularly 60 to 100% by mass. Examples of other monomer units include propylene units, 1-butene units, 2-methylpropylene units, 1-pentene units, 3-methyl-1-butene units, 1-hexene units, 4-methyl-1-pentene units, and 1-octene units. Preferred are α-olefin units having 3 to 8 carbon atoms and a carbon-carbon double bond at the terminal carbon atom, such as propylene units, 1-butene units, 1-hexene units, and 1-octene units. The polymer block made of ethylene in component (B) may be one in which only one type of α-olefin is copolymerized with ethylene, or two or more types of α-olefins are copolymerized with ethylene.

[0050] The block containing α-olefin in the ethylene-α-olefin block copolymer of component (B) may be exemplified by those having propylene unit, 1-butene unit, 2-methylpropylene unit, 1-pentene unit, 3-methyl-1-butene unit, 1-hexene unit, 4-methyl-1-pentene unit, or 1-octene unit as a constituent unit of the α-olefin unit, and is preferably an α-olefin unit having 3 to 8 carbon atoms and having a carbon-carbon double bond at the terminal carbon atom of a propylene unit, 1-butene unit, 1-hexene unit, or 1-octene unit. From the viewpoint of low-temperature impact resistance, it is preferable that the block containing α-olefin in component (B) contains an ethylene unit in addition to the α-olefin unit. In this case, the block containing α-olefin may be one in which only one type of α-olefin is copolymerized with ethylene, or two or more types of α-olefins are copolymerized with ethylene.

[0051] The α-olefin-containing block in the ethylene-α-olefin block copolymer of component (B) may have, in addition to the α-olefin units and ethylene units described above, other monomer units such as monomer units based on non-conjugated dienes (non-conjugated diene units). The non-conjugated diene unit may be a chain non-conjugated diene unit such as 1,4-hexadiene unit, 1,6-octadiene unit, 2-methyl-1,5-hexadiene unit, 6-methyl-1,5-heptadiene unit, or 7-methyl-1,6-octadiene unit; or a cyclic non-conjugated diene unit such as cyclohexadiene unit, dicyclopentadiene unit, methyltetrahydroindene unit, 5-vinylnorbornene unit, 5-ethylidene-2-norbornene unit, 5-methylene-2-norbornene unit, 5-isopropylidene-2-norbornene unit, or 6-chloromethyl-5-isopropenyl-2-norbornene unit. Among these, dicyclopentadiene unit and 5-ethylidene-2-norbornene unit are preferred.

[0052] When the ethylene-α-olefin block copolymer of component (B) contains other monomer units such as non-conjugated diene units, the content thereof is usually 10 mass % or less, preferably 5 mass % or less, based on the total mass of component (B).

[0053] The ethylene-α-olefin block copolymer of component (B) used in the thermoplastic elastomer composition of the present invention may, for example, be an ethylene-α-olefin block copolymer having a polymer block made of ethylene and an ethylene-α-olefin copolymer block. Specific examples of the ethylene-α-olefin block copolymer include block copolymers containing a polymer block made of ethylene and an ethylene-α-olefin copolymer block such as an ethylene-1-butene copolymer, an ethylene-1-hexene copolymer, an ethylene-1-octene copolymer, an ethylene-propylene-1-butene copolymer, an ethylene-propylene-1-hexene copolymer, or an ethylene-propylene-1-octene copolymer. Among these, from the viewpoint of tensile strength, it is preferable that component (B) is an ethylene-1-octene block copolymer containing a polymer block made of ethylene and an ethylene-1-octene copolymer block.

[0054] The melt flow rate (190°C, load 21.18N) of component (B) is not limited, but is usually 10g / 10min or less, and from the viewpoint of strength, it is preferably 8.0g / 10min or less, more preferably 5.0g / 10min or less, and even more preferably 3.0g / 10min or less. The melt flow rate (190°C, load 21.18N) of component (B) is usually 0.01g / 10min or more, and from the viewpoint of fluidity, it is preferably 0.05g / 10min or more, more preferably 0.10g / 10min or more. The melt flow rate of component (B) is measured according to ASTM D1238 under the conditions of 190°C and load 21.18N.

[0055] From the viewpoint of low-temperature impact resistance, the density of component (B) is preferably 0.880 g / cm 3 More preferably, it is 0.870 g / cm or less. 3 On the other hand, the lower limit is not particularly limited, but is usually 0.850 g / cm 3 The density of component (B) can be measured according to ASTM D792.

[0056] The ethylene-α-olefin block copolymer of component (B) can be synthesized according to the methods disclosed in JP-A-2007-529617, JP-A-2008-537563, and JP-A-2008-543978. For example, the copolymer can be produced by preparing a composition containing a mixture or reaction product obtained by combining a first olefin polymerization catalyst, a second olefin polymerization catalyst capable of preparing a polymer having different chemical or physical properties from the polymer prepared by the first olefin polymerization catalyst under the same polymerization conditions, and a chain shuttling agent, and contacting the composition with the ethylene and α-olefin under addition polymerization conditions.

[0057] For the polymerization of the ethylene-α-olefin block copolymer of component (B), a continuous solution polymerization method is preferably applied. In the continuous solution polymerization method, the catalyst components, the chain shuttling agent, the monomers, and optionally the solvent, the auxiliary, the scavenger and the polymerization aid are continuously fed into the reaction zone, and the polymer product is continuously taken out therefrom. In this case, the length of each block of the ethylene-α-olefin block copolymer can be changed by controlling the ratio and type of the catalyst, the ratio and type of the chain shuttling agent, the polymerization temperature, etc.

[0058] Component (B) may be a commercially available product. Examples of commercially available products of component (B) include the "Engage (registered trademark)-XLT" series and "INFUSE (registered trademark)" series manufactured by Dow Chemical Company, the "Solumer (registered trademark)" series manufactured by SK Corporation, the "Tafmer (registered trademark)" series and "Mitsui EPT" manufactured by Mitsui Chemicals, Inc., "JSR EPR" manufactured by JSR Corporation, "Esprene (registered trademark)" manufactured by Sumitomo Chemical Co., Ltd., and "Keltan (registered trademark)" manufactured by LANXESS.

[0059] The ethylene-α-olefin copolymer of component (B) may be used alone or in combination of two or more types having different copolymer component compositions, physical properties, etc.

[0060] <Ingredient (C)> As described above, the thermoplastic elastomer composition of the present invention is preferably produced using an organic peroxide as component (C). The organic peroxide as component (C) acts as a crosslinking agent in the dynamic heat treatment. This dynamic heat treatment can reduce the gloss of molded products such as airbag storage covers made of the thermoplastic elastomer composition of the present invention, resulting in a particularly good appearance.

[0061] As the organic peroxide of component (C), both aromatic organic peroxides and aliphatic organic peroxides can be used. Specific examples of the peroxides include dialkyl peroxides such as di-t-butyl peroxide, t-butylcumyl peroxide, dicumyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, 2,5-dimethyl-2,5-di(t-butylperoxy)-3-hexyne, 1,3-bis(t-butylperoxyisopropyl)benzene, and 1,1-di(t-butylperoxy)-3,3,5-trimethylcyclohexane; peroxy esters such as t-butyl peroxybenzoate, t-butylperoxyisopropyl carbonate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, and 2,5-dimethyl-2,5-di(benzoylperoxy)-3-hexyne; and hydroperoxides such as acetyl peroxide, lauroyl peroxide, benzoyl peroxide, p-chlorobenzoyl peroxide, and 2,4-dichlorobenzoyl peroxide. Among these, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane is preferred. These may be used alone or in combination of two or more.

[0062] <Ingredient (D)> As described above, the thermoplastic elastomer composition of the present invention is preferably produced by using the crosslinking aid of component (D) together with the above-mentioned component (C). Component (D) acts as a crosslinking aid in dynamic heat treatment.

[0063] Examples of the crosslinking aid of component (D) include peroxide aids such as sulfur, p-quinone dioxime, p-dinitrosobenzene, and 1,3-diphenyl guanidine; polyfunctional vinyl compounds such as divinylbenzene, triallyl cyanurate, triallyl isocyanurate, and diallyl phthalate; and polyfunctional (meth)acrylate compounds such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and allyl (meth)acrylate. These may be used alone or in combination of two or more.

[0064] <Ingredient (E)> The thermoplastic elastomer composition of the present invention may contain a styrene-conjugated diene block copolymer and / or a hydrogenated product thereof as component (E).

[0065] Suitable conjugated dienes in the styrene-conjugated diene block copolymer and / or its hydrogenated product of component (E) are butadiene, isoprene or a mixture thereof. Examples of component (E) include styrene-butadiene block copolymer and / or its hydrogenated product. Examples of hydrogenated styrene-butadiene block copolymer include partially hydrogenated styrene-butadiene-butylene-styrene copolymer (SBBS) and substantially completely hydrogenated styrene-ethylene-butylene-styrene copolymer (SEBS). Examples of component (E) include styrene-ethylene-propylene-styrene copolymer (SEPS), which is a hydrogenated product of styrene-isoprene block copolymer, and hydrogenated products of styrene-butadiene-isoprene block copolymer.

[0066] The styrene unit content of the styrene-conjugated diene block copolymer and / or its partially hydrogenated product or fully hydrogenated product is not particularly limited, but from the viewpoints of strength and heat resistance, it is preferably 5% by mass or more, more preferably 8% by mass or more, and even more preferably 10% by mass or more. Also, from the viewpoints of flexibility and impact resistance, the styrene unit content is preferably 70% by mass or less, more preferably 55% by mass or less, and even more preferably 40% by mass or less.

[0067] The conjugated diene in component (E) has a 1,2-microstructure analyzed by NMR method of preferably 60 mol % or less, more preferably 45 mol % or less. The 1,2-microstructure is preferably below the above upper limit from the viewpoints of moldability and flexibility, and is also preferred from the viewpoint of not excessively proceeding with the crosslinking reaction due to dynamic heat treatment. From the viewpoint of utilizing the crosslinking reaction in component (E), when component (E) is a hydrogenated product of a styrene-conjugated diene block copolymer, the hydrogenation rate is preferably 95% or less, more preferably 90% or less, and even more preferably 85% or less.

[0068] When the conjugated diene in component (E) is a mixture of isoprene and butadiene, the mass ratio (isoprene / butadiene) is generally 99 / 1 to 1 / 99, preferably 90 / 10 to 30 / 70, and more preferably 80 / 20 to 40 / 60.

[0069] From the viewpoint of releasability, the weight average molecular weight (Mw) of component (E) is preferably 50,000 or more, more preferably 80,000 or more, and even more preferably 100,000 or more. From the viewpoint of fluidity and dispersibility, the weight average molecular weight (Mw) of component (E) is preferably 500,000 or less, more preferably 450,000 or less, even more preferably 400,000 or less, and particularly preferably 350,000 or less.

[0070] The weight average molecular weight (Mw) of the component (E) is measured by gel permeation chromatography (GPC), and can be measured, for example, under the following conditions. Equipment: Tosoh Corporation "HLC-8220GPC(R)" Column: Tosoh Corporation "TSKgel Super HM-M (6.0 mm I.D. x 15 cm x 2+G)" Detector: Differential refractive index detector (RI / built-in) Solvent: Chloroform Temperature: 40℃ Flow rate: 0.25mL / min Injection volume: 0.1 mass% x 20 μL Calibration sample: monodisperse polystyrene Calibration method: Polystyrene equivalent Calibration curve approximation: cubic (hyperbola) Exclusion limit setting time: 12 minutes

[0071] A method for producing the styrene-conjugated diene block copolymer of component (E) is, for example, a method for synthesizing the styrene-conjugated diene block copolymer in an inert solvent using a lithium catalyst by the method described in JP-B-40-23798. A method for producing a hydrogenated product of the styrene-conjugated diene block copolymer is, for example, a method for synthesizing the styrene-conjugated diene block copolymer by the above method, and then hydrogenating the copolymer in an inert solvent in the presence of a hydrogenation catalyst by the methods described in JP-B-42-8704, JP-B-43-6636, JP-A-59-133203, and JP-A-60-79005.

[0072] The styrene-conjugated diene block copolymer and / or its hydrogenated product of component (E) may be commercially available. Examples of commercially available styrene-conjugated diene block copolymers include Kraton (registered trademark) D manufactured by Kraton Polymers and Globalprene (registered trademark) manufactured by LCY. Examples of partially hydrogenated styrene-conjugated diene block copolymers include Tuftec (registered trademark) P manufactured by Asahi Kasei Corporation. Examples of fully hydrogenated styrene-conjugated diene block copolymers include Kraton (registered trademark) G manufactured by Kraton Polymers, Septon (registered trademark) manufactured by Kuraray Co., Ltd., and Tuftec (registered trademark) manufactured by Asahi Kasei Corporation.

[0073] The styrene-conjugated diene block copolymer and / or hydrogenated product thereof as component (E) may be used alone or in combination of two or more types having different copolymer component compositions, physical properties, etc.

[0074] <Component (F)> From the viewpoint of improving moldability, the thermoplastic elastomer composition of the present invention preferably contains a hydrocarbon-based rubber softener as component (F).

[0075] Examples of the hydrocarbon-based rubber softener of component (F) include mineral oil-based softeners and synthetic resin-based softeners, but mineral oil-based softeners are preferred in terms of compatibility with other components. Mineral oil-based softeners are generally mixtures of aromatic hydrocarbons, naphthenic hydrocarbons, and paraffinic hydrocarbons, and those in which 50% or more of the total carbon atoms are paraffinic hydrocarbons are called paraffinic oils, those in which 30-45% of the total carbon atoms are naphthenic hydrocarbons, and those in which 35% or more of the total carbon atoms are aromatic hydrocarbons are called aromatic oils. Of these, it is preferable to use paraffinic oils in the present invention.

[0076] The kinematic viscosity (ASTMD 445 / JIS K2283) of the hydrocarbon rubber softener of component (F) at 40°C is not particularly limited, but is preferably 20 cSt or more, more preferably 50 cSt or more, and is preferably 800 cSt or less, more preferably 600 cSt or less. The flash point (COC method) of the hydrocarbon rubber softener is preferably 200°C or more, more preferably 250°C or more.

[0077] The hydrocarbon rubber softener of component (F) may be a commercially available product. Examples of commercially available products of component (F) include Nippon Oil Polybutene (registered trademark) HV series manufactured by JX Nippon Oil & Energy Corporation and Diana (registered trademark) Process Oil PW series manufactured by Idemitsu Kosan Co., Ltd., and any of these may be appropriately selected and used.

[0078] The hydrocarbon-based rubber softeners of component (F) may be used alone or in combination of two or more kinds.

[0079] <Mixing ratio> The blending ratio of the raw materials for the thermoplastic elastomer composition of the present invention will be described below.

[0080] The content of component (B) in the thermoplastic elastomer composition of the present invention is usually 40 parts by mass or more, preferably 50 parts by mass or more, more preferably 60 parts by mass or more, per 100 parts by mass of component (A) from the viewpoint of low-temperature impact properties, and usually 200 parts by mass or less, preferably 150 parts by mass or less, more preferably 120 parts by mass or less, from the viewpoint of rigidity and tensile strength of a molded article.

[0081] When component (C) is used in the thermoplastic elastomer composition of the present invention, the content of component (C) is usually 0.01 part by mass or more, preferably 0.05 part by mass or more, more preferably 0.10 part by mass or more, from the viewpoint of low gloss, when the total of components (A) and (B) is taken as 100 parts by mass, while the content of component (C) is usually 1.00 part by mass or less, preferably 0.80 part by mass or less, more preferably 0.60 part by mass or less, from the viewpoint of low-temperature impact resistance and flow mark resistance. When the thermoplastic elastomer composition of the present invention further contains component (E) and / or component (F), the content of component (C) described above may be applied based on 100 parts by mass of the total of components (A), (B), (E), and (F).

[0082] When component (D) is used in the thermoplastic elastomer composition of the present invention, the content of component (D) is usually 0.01 part by mass or more, preferably 0.05 part by mass or more, more preferably 0.10 part by mass or more, from the viewpoint of low gloss, when the total of components (A) and (B) is taken as 100 parts by mass, while from the viewpoint of flow mark resistance, it is usually 1.00 part by mass or less, preferably 0.80 part by mass or less, more preferably 0.60 part by mass or less. When the thermoplastic elastomer composition of the present invention further contains component (E) and / or component (F), the content of component (D) described above may be applied based on 100 parts by mass of the total of components (A), (B), (E), and (F).

[0083] When the thermoplastic elastomer composition of the present invention contains component (E), the content thereof is usually 1 part by mass or more, preferably 5 parts by mass or more, more preferably 10 parts by mass or more, per 100 parts by mass of component (A) from the viewpoint of low-temperature impact properties, and usually 100 parts by mass or less, preferably 80 parts by mass or less, more preferably 60 parts by mass or less, from the viewpoint of rigidity and tensile strength of the molded article.

[0084] When the thermoplastic elastomer composition of the present invention contains component (F), the content thereof is usually 1 part by mass or more, preferably 5 parts by mass or more, more preferably 10 parts by mass or more, per 100 parts by mass of component (A), from the viewpoints of low-temperature impact resistance, fluidity, and flow mark resistance, and is usually 100 parts by mass or less, preferably 80 parts by mass or less, more preferably 60 parts by mass or less, from the viewpoints of rigidity, tensile strength, and oil bleeding of the molded article.

[0085] <Other ingredients> The thermoplastic elastomer composition of the present invention may contain other components as required within the range that does not impair the effects of the present invention.

[0086] Examples of other components include resins such as thermoplastic resins and elastomers other than components (A), (B), and (E), antioxidants, fillers, heat stabilizers, weathering aids, light stabilizers, ultraviolet absorbers, neutralizing agents, lubricants, antifogging agents, antiblocking agents, slip agents, dispersants, colorants, flame retardants, antistatic agents, conductivity imparting agents, metal deactivators, molecular weight regulators, antibacterial agents, antifungal agents, fluorescent brighteners, etc. These may be used alone or in combination of two or more.

[0087] Examples of thermoplastic resins other than component (A) include polyphenylene ether resins, polyamide resins such as nylon 6 and nylon 66, polyester resins such as polyethylene terephthalate and polybutylene terephthalate, polyoxymethylene resins such as polyoxymethylene homopolymers and polyoxymethylene copolymers, polymethyl methacrylate resins, and polyolefin resins (excluding those corresponding to component (A) or component (B)). Examples of elastomers other than components (B) and (E) include styrene elastomers (excluding those corresponding to component (E)), polyester elastomers, and polybutadiene.

[0088] Examples of the antioxidant include phenol-based antioxidants, phosphite-based antioxidants, and thioether-based antioxidants. When an antioxidant is used, it is usually used in the range of 0.01 to 3.0 parts by mass per 100 parts by mass of the total of component (A), component (B), and optionally used components (E) and (F).

[0089] Examples of the filler include glass fiber, hollow glass spheres, carbon fiber, talc, calcium carbonate, mica, potassium titanate fiber, silica, metal soap, titanium dioxide, and carbon black. When a filler is used, it is usually used in an amount of 0.1 to 50 parts by mass per 100 parts by mass of the total of component (A), component (B), and optionally used components (E) and (F).

[0090] [Method of producing thermoplastic elastomer composition] The thermoplastic elastomer composition of the present invention is preferably produced by dynamically heat treating a composition containing predetermined amounts of component (A) and component (B), and optionally component (E), component (F) and other components, in the presence of component (C) and component (D).

[0091] In the present invention, the term "dynamic heat treatment" refers to kneading in a molten or semi-molten state in the presence of component (C) and component (D). This dynamic heat treatment is preferably performed by melt kneading, and the mixing and kneading device used therefor may be, for example, a non-open type Banbury mixer, a mixing roll, a kneader, or a twin-screw extruder. Among these, it is preferable to use a twin-screw extruder.

[0092] A preferred embodiment of the production method using a twin-screw extruder is a method in which a mixture containing a part of component (A), component (B), component (C), component (D), component (E), component (F) used as necessary, and other components is melt-kneaded while being fed into a cylinder from a raw material feed port (hopper) (hereinafter sometimes referred to as the "first hopper") on the more upstream side of a twin-screw extruder having multiple raw material feed ports, and the remaining amount of component (A) is fed into the cylinder from a raw material feed port (hopper) (hereinafter sometimes referred to as the "second hopper") located on the more downstream side separate from the first hopper and further heat-treated to produce a partially crosslinked thermoplastic elastomer. Here, the second hopper that feeds the remaining amount of component (A) is preferably a raw material feed port located downstream of L / 2, where L is the length from the most upstream raw material feed port (usually the first hopper) to the most upstream mixture outlet. However, if the second hopper is located too far downstream, the component (A) supplied from the second hopper will not be sufficiently dispersed, and therefore, the second hopper is preferably located at least L / 10 upstream of the outlet of the mixture. Furthermore, the raw material supplied from the second hopper may be at least a portion of component (B), component (E) and component (F) in addition to the remainder of component (A).

[0093] In this manner, by dynamically heat treating a mixture of a part of component (A), component (B), component (C), component (D), component (E) and component (F) to partially crosslink the mixture and then adding the remainder of component (A), component (A) added later is less susceptible to molecular chain scission by radicals, and the thermoplastic elastomer composition has high tensile strength and an improved die swell ratio.

[0094] From the viewpoint of improving the mechanical strength and die swell ratio of the obtained composition, the initial charge amount of component (A) (amount fed from the first hopper) is preferably 90 parts by mass or less, more preferably 80 parts by mass or less, and even more preferably 70 parts by mass or less, where the total amount of component (A) is 100 parts by mass. On the other hand, from the viewpoint of production stability during production, the initial charge amount of component (A) (amount fed from the first hopper) is preferably 10 parts by mass or more, more preferably 20 parts by mass or more, and even more preferably 30 parts by mass or more. Even when components (B), (E), and (F) are fed in portions, they are preferably fed in portions in the same ratio as component (A).

[0095] The temperature when the dynamic heat treatment is carried out is usually 80 to 300° C., and preferably 100 to 250° C. The time for which the dynamic heat treatment is carried out is usually 0.1 to 30 minutes.

[0096] When the thermoplastic elastomer composition of the present invention is produced by performing dynamic heat treatment using a twin-screw extruder, it is preferable to extrude the composition while maintaining the relationship of the following formula (1) between the barrel radius R (mm), the screw rotation speed N (rpm), and the discharge rate Q (kg / h) of the twin-screw extruder, and it is more preferable to extrude the composition while maintaining the relationship of the following formula (2). 2.6 <NQ / R 3 <22.6 …(1) 3.0 <NQ / R 3 <20.0 …(2)

[0097] It is preferable that the above relationship between the barrel radius R (mm), screw rotation speed N (rpm), and discharge rate Q (kg / hour) of the twin-screw extruder is larger than the above lower limit value in order to efficiently produce the thermoplastic elastomer composition, while it is preferable that the above relationship is smaller than the above upper limit value in order to suppress heat generation due to shear and to prevent the generation of foreign matter that causes a defective appearance.

[0098] [Molded products] <Ingredient method> A molded article can be obtained by molding the thermoplastic elastomer resin composition of the present invention. The thermoplastic elastomer composition of the present invention can be molded into a molded article by a normal injection molding method or, if necessary, by various molding methods such as gas injection molding, injection compression molding, short shot foam molding, etc. Among them, it is preferable to produce a molded article by injection molding, and the molding conditions when performing injection molding are as follows. The molding temperature when injection molding a molded product is generally 150 to 300° C., and preferably 160 to 280° C. The injection pressure is generally 5 to 100 MPa, and preferably 10 to 80 MPa. The mold temperature is generally 0 to 80° C., and preferably 20 to 60° C.

[0099] <Application> The molded article thus obtained can be used, for example, as an airbag storage cover, which is suitably used as an airbag storage cover for an airbag system that is activated and inflated upon sensing the impact or deformation of a high-speed moving object such as an automobile in a collision accident or the like. The airbag storage cover of the present invention can be suitably used as a driver's airbag storage cover, a passenger's airbag storage cover, a pedestrian airbag storage cover, a knee airbag storage cover, a side airbag storage cover, a curtain airbag storage cover, etc.

[0100] [Physical properties of thermoplastic elastomer compositions and molded products] <mfr> The thermoplastic elastomer composition of the present invention is also excellent in moldability. Specifically, the melt flow rate (MFR) according to ISO 1133 (2011) at a temperature of 230°C and a measurement load of 21.18 N is usually 0.5 to 50 g / 10 min, preferably 1 to 40 g / 10 min, and more preferably 2 to 30 g / 10 min.

[0101] <Tensile strength at break> The thermoplastic elastomer composition of the present invention also has excellent tensile strength. Specifically, the tensile strength at break measured using a 1A dumbbell as specified in ISO 37 (2011) at a pulling speed of 500 mm / min in an atmosphere of 23°C is usually 10 MPa or more, preferably 13 MPa or more, and more preferably 15 MPa or more.

[0102] <Elongation at break> The thermoplastic elastomer composition of the present invention also has excellent elongation at break. Specifically, the elongation at break measured using a 1A dumbbell as specified in ISO 37 (2011) at a tensile speed of 500 mm / min in an atmosphere of 23° C. is usually 500% or more, preferably 600% or more, and more preferably 700% or more.

[0103] <Low temperature impact resistance> The thermoplastic elastomer composition of the present invention has excellent low-temperature impact resistance. In the present invention, the low-temperature impact resistance is evaluated by the Izod impact strength at -45°C by the method shown in the Examples below. In the present invention, the Izod impact strength at -45°C is 50 kJ / m 2 It is preferable that the concentration is 60 kJ / m or more. 2 More preferably, it is 70 kJ / m or more. 2 More preferably, it is equal to or greater than this.

[0104] <Flow mark resistance> Molded articles obtained from the thermoplastic elastomer composition of the present invention are excellent in resistance to flow marks, with almost no flow marks being observed. As described above, the thermoplastic elastomer composition of the present invention tends to have good flow mark properties when the die swell ratio is large. That is, it is considered that a large die swell ratio of 1.10 or more contributes to the stability of the flow front in the mold during injection molding, thereby improving the flow mark properties. EXAMPLES

[0105] The present invention will be described in more detail below using examples, but the present invention is not limited to the following examples as long as it does not exceed the gist of the invention. The values ​​of various production conditions and evaluation results in the following examples are meant as preferred upper or lower limit values ​​in the embodiment of the present invention, and the preferred range may be a range defined by a combination of the above-mentioned upper or lower limit values ​​and the values ​​of the following examples or values ​​of the examples.

[0106] [Raw materials for manufacturing thermoplastic elastomer compositions] <Component (A)> A-1: Propylene block copolymer (obtained by polymerizing propylene homopolymer in the first step, followed by polymerizing propylene-ethylene copolymer in the second step) Novatec (registered trademark) PP BC06NCA manufactured by Japan Polypropylene Corporation MFR (ISO 1133 (2011)): 60g / 10min (measurement conditions: 230℃, load 21.18N) Propylene unit content: 96% by mass Ethylene unit content: 4% by mass

[0107] <Ingredient (B)> B-1: Ethylene-1-octene block copolymer (a block copolymer having a polymer block composed of ethylene and a block of ethylene-1-octene copolymer) Dow Chemical Company Engage® XLT8677 Crystal melting peak temperature: 119℃ Heat of crystal fusion: 37J / g MFR (ASTM D1238): 0.5g / 10min (measurement conditions: 190℃, load 21.18N) (catalog value) Glass transition temperature (DSC method): -67℃ Density (ASTM D792): 0.870g / cm 3 (catalog value)

[0108] B-2: Ethylene-propylene-ethylidene norbornene terpolymer rubber Mitsui Chemicals Mitsui EPT3092PM Mooney Viscosity ML(1+4)125℃(ASTM D1646):61(catalog value) Ethylene unit content (ASTM D3900): 65% by mass (catalog value) Ethylidene norbornene unit content (ASTM D6047): 4.6% by mass (catalog value)

[0109] B-3: Ethylene-1-octene random copolymer Dow Chemical Company Engage® 8180 Crystal melting peak temperature: No peak at 110-125℃ Heat of crystal fusion: 0 MFR (ASTM D1238): 0.5g / 10min (measurement conditions: 190℃, load 21.18N) (catalog value) Density (ASTM D792): 0.863g / cm 3 (catalog value)

[0110] <Ingredient (C)> C-1: Trigonox 101-40C (a mixture of 40% by mass of 2,5-dimethyl-2,5-di(t-butylperoxy)hexane and 60% by mass of calcium carbonate) manufactured by Nouryon Chemical Industries, Ltd.

[0111] <Ingredient (D)> D-1: Mitsubishi Chemical Corporation Acryester TMP (trimethylolpropane trimethacrylate) D-2: Divinylbenzene (mixture of 55% divinylbenzene and 45% ethylvinylbenzene) manufactured by Wako Pure Chemical Industries, Ltd.

[0112] <Ingredient (E)> E-1: Styrene-butadiene-styrene block copolymer Kraton Polymers, Inc. Kraton (registered trademark) D1101J Weight average molecular weight (Mw): 160,000 Styrene unit content: 31% by mass (catalog value) Conjugated diene unit content: 69% by mass (catalog value) 1,2-microstructure of conjugated diene component: 12 mol% Hydrogenation rate: 0%

[0113] <Component (F)> F-1: Paraffin oil Idemitsu Kosan Diana (registered trademark) Process Oil PW90 Kinematic viscosity at 40℃: 95.54cSt Pour point: -15℃ Flash point: 272℃

[0114] [Method of evaluating thermoplastic elastomer composition] 1) Melt flow rate (MFR) Measured in accordance with ISO 1133 (2011) at 230°C and a load of 21.18N.

[0115] 2) Tensile strength at break / elongation at break Using an in-line screw type injection molding machine (Sumitomo Wiring Systems, Ltd., "SE100DU"), a test piece for a tensile test (a sheet of 2 mm thick x 120 mm wide x 80 mm long) was molded from the thermoplastic elastomer composition at an injection speed of 30 mm / s, a cylinder temperature of 220°C, and a mold temperature of 40°C, and then punched out in accordance with ISO 37 (2011) (1A dumbbell). The tensile strength at break (unit: MPa) and elongation at break (unit: %) of the punched test piece were measured at a tensile speed of 500 mm / min and an atmosphere of 23°C using Shimadzu Corporation's Autograph Precision Universal Testing Machine "AGS-H".

[0116] 3) Flexural modulus Using an in-line screw type injection molding machine (Sumitomo Wiring Systems, Ltd., "SE100DU"), the thermoplastic elastomer composition was molded into a multipurpose evaluation test piece A (180 mm long dumbbell) conforming to ISO 3167 (2002) at an injection speed of 30 mm / s, a cylinder temperature of 220°C, and a mold temperature of 40°C. The ends of the dumbbell were cut off to prepare a test piece for measuring the flexural modulus (4 mm thick x 10 mm wide x 80 mm long). The flexural modulus was measured at a speed of 2 mm / min using a Pentograph B-2 manufactured by Toyo Seiki Co., Ltd., in accordance with ISO 178 (2010).

[0117] 4) Die swell ratio Measurements were performed during the extrusion process of the thermoplastic elastomer composition using a Capillograph 1D (JIS K7199) manufactured by Toyo Seiki Seisakusho Co., Ltd. under the following conditions. Test temperature: 210℃ L / D: 10 (D=1mm) Shear rate: 243 / s The die swell ratio was calculated by the following formula (I). St=Dm / Dt (I) St, Dm, and Dt indicate the following. St: Die swell ratio Dm: diameter of extrusion sample measured at test temperature, 10 mm below the die exit (mm) Dt: diameter of the capillary die measured at the test temperature (mm)

[0118] 5) Glossiness Using an in-line screw type injection molding machine ("SE100DU" manufactured by Sumitomo Wiring Systems, Ltd.), a test piece for measuring gloss (a sheet having a thickness of 2 mm, a width of 120 mm, and a length of 80 mm) was molded from the thermoplastic elastomer composition at an injection speed of 30 mm / s, a cylinder temperature of 220°C, and a mold temperature of 40°C. The gloss was measured at an incidence angle of 60° in accordance with ISO 2813.

[0119] 6) Low temperature impact resistance (Izod impact strength) The thermoplastic elastomer composition was molded into a test piece for Izod impact strength, measuring 4 mm thick x 10 mm wide x 80 mm long, using an in-line screw type injection molding machine (Sumitomo Wiring Systems, Ltd., "SE100DU") at an injection speed of 30 mm / s, a cylinder temperature setting of 220°C, and a mold temperature of 40°C. After that, a notch was made in the dumbbell (notch dimensions and evaluation method conformed to ISO 180 (2013)), and measurements were made at -45°C.

[0120] 7) Flow mark properties The flow mark property was evaluated by molding a test piece for measuring gloss (a sheet having a thickness of 2 mm, a width of 120 mm, and a length of 80 mm) from the thermoplastic elastomer composition using an in-line screw type injection molding machine ("SE100DU" manufactured by Sumitomo Wiring Systems, Ltd.) at an injection speed of 30 mm / s, a cylinder temperature setting of 220°C, and a mold temperature of 40°C. The appearance of the test piece was visually observed and evaluated according to the following criteria. Judgment criteria 1: Flow marks are noticeable and the appearance is very poor. 2: Flow marks are noticeable and the appearance is poor. 3: Flow marks are observed. 4: A few flow marks are visible. 5: No flow marks observed.

[0121] [Example 1] A portion of component (A-1): 20 parts by mass, component (B-1): 50 parts by mass, component (C-1): 0.40 parts by mass, and component (D-1): 0.40 parts by mass were blended with 0.1 parts by mass of an antioxidant (manufactured by BASF Japan Ltd., product name Irganox (registered trademark) 1010) and 2 parts by mass of a black pigment (carbon concentration 40% by mass) per 100 parts by mass of the total of components (A-1) and (B-1) in a Henschel mixer for 1 minute, and the resulting mixture was mixed with the above mixture. The mixture was fed into a 1-way twin screw extruder (Kobe Steel "TEX30α", L / D=45, number of cylinder blocks: 13) from the first feed port at a rate of 14 kg / hr, heated to a range of 180-210°C, melt-kneaded, and simultaneously fed from the second feed port provided in the middle of the extruder cylinder with the remaining component (A-1): 30 parts by mass at a rate of 6 kg / hr, kneaded, and pelletized to produce a thermoplastic elastomer composition. The evaluation results of the obtained thermoplastic elastomer composition are shown in Table 1. The first supply port is provided in the most upstream cylinder block of the co-rotating twin-screw extruder, and the second supply port is provided in the ninth cylinder block from the upstream.

[0122] [Examples 2 to 4, Comparative Examples 1 to 7] Pellets of a thermoplastic elastomer composition were obtained in the same manner as in Example 1, except that the raw material composition was as shown in Table 1. The obtained thermoplastic elastomer composition was evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.

[0123] In Table 1, "A-1 (※1)" is the amount of component (A-1) fed from the first feed port, and "A-1 (※2)" is the amount of component (A-1) fed from the second feed port. Also, "-" in the raw material blend column indicates that the component was not used.

[0124] [Table 1]

[0125] [Consideration] From Table 1, it can be seen that the thermoplastic elastomer compositions of Examples 1 to 4, which have die swell ratios, glossiness, and flexural modulus within the ranges specified in the present invention, have low glossiness, good flow mark resistance, and excellent design properties, and are also excellent in low-temperature impact resistance.

[0126] In contrast, Comparative Examples 1 and 2 have a large die swell ratio, but have high gloss and poor design. In Comparative Examples 3 to 6, the die swell ratio was less than 1.10, flow marks were observed, and the design was poor. In Comparative Example 7, the die swell ratio was 1.10 or more, and the flow mark resistance was excellent, but the gloss level was high and the design was poor. [Industrial Applicability]

[0127] The thermoplastic elastomer composition of the present invention is suitable for various applications since it has excellent design while maintaining low-temperature impact resistance. For example, the thermoplastic elastomer composition of the present invention is useful as automobile interior parts such as airbag storage covers, instrument panels, center panels, center console boxes, door trims, pillars, assist grips, and handles, automobile exterior parts such as mudguards and grommets, home appliance parts, building materials, and furniture. Among these, the thermoplastic elastomer composition of the present invention is particularly useful as an airbag storage cover, and among airbag storage covers, it is suitable as an airbag storage cover for an airbag system that operates by detecting the impact or deformation of a high-speed moving body such as an automobile in a collision accident, and protects the occupant by inflating and deploying.< / mfr>

Claims

1. A thermoplastic elastomer composition comprising the following components (A) and (B): The die swell ratio (test temperature 210°C, shear rate 243 / s) in a capillary rheometer (JIS K7199) is 1.10 or more, A gloss test piece made of the thermoplastic elastomer composition has a gloss of 50% or less as measured at an incidence angle of 60° in accordance with ISO 2813; and A thermoplastic elastomer composition, wherein a flexural modulus measurement test piece made of the thermoplastic elastomer composition has a flexural modulus of 100 to 700 MPa as measured in accordance with ISO 178 (2010). Component (A): Propylene-based block copolymer Component (B): Ethylene / α-olefin copolymer

2. 2. The thermoplastic elastomer composition according to claim 1, wherein the α-olefin of component (B) has 4 to 8 carbon atoms.

3. 3. The thermoplastic elastomer composition according to claim 1, wherein the ethylene / α-olefin copolymer of component (B) is an ethylene / α-olefin block copolymer.

4. The thermoplastic elastomer composition according to claim 3, wherein the ethylene / α-olefin block copolymer is an ethylene / α-olefin block copolymer comprising a polymer block made of ethylene and an ethylene / α-olefin copolymer block.

5. The thermoplastic elastomer composition according to claim 4, wherein the ethylene / α-olefin block copolymer has a crystalline melting peak at 110 to 125° C. and a crystalline melting heat of 20 to 60 J / g.

6. An injection-molded article obtained by injection molding the thermoplastic elastomer composition according to any one of claims 1 to 5.

7. An airbag storage cover using the thermoplastic elastomer composition according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • High-tension rubber composition

    JP2002020547A

  • Method for manufacturing olefinic thermoplastic elastomer composition

    JP2002069202A

  • Propylene-ethylene block copolymer

    JP2003327643A

  • Thermoplastic elastomer composition for airbag cover, and the airbag cover

    JP2013142140A

  • Polypropylene resin composition for foam molding and foam molded body

    JP2016056264A